Analisis Pengaruh Gaya Hidup Digital, Kepercayaan, dan Promosi terhadap Keputusan Mahasiswa Politeknik Negeri Padang dalam Menggunakan ShopeePay - Harjimen, Saskia; Afni, Zalida; Ulfa Nely, Meri (Jurusan Akuntansi Politeknik Negeri Padang, 2025)
This study aims to analyze the influence of digital lifestyle, trust, and promotion on the decision of Padang State Polytechnic students to use ShopeePay. The development of digital technology has changed people's transaction patterns, including students who now widely use digital wallets such as ShopeePay. However, there has been a decline in usage, so it is necessary to study the factors that influence the decision to use. This study used a quantitative approach with an associative design. Data were collected through an online questionnaire from 150 active students selected by purposive sampling. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results showed that digital lifestyle and trust had a positive and significant influence on the decision to use ShopeePay, while promotion had no significant influence. The results of this study indicate that the decision to use ShopeePay is more influenced by the suitability of digital lifestyle and the level of trust in the system, rather than by promotional factors. This confirms that students prioritize aspects of convenience, habit, and trust in using digital wallet services compared to temporary promotional benefits